Estudo das propriedades fotoluminescentes e estruturais de materiais híbridos contendo polímero derivado de polifluoreno pelo processo sol-gel - Santos, Thays Cristina Fernandes dos [UNIFESP] (2014)
The present work studied polyfluorenes based in materials with two different steps. The first one, a comparative study of two oligomers was done, with polyfluorenes with different amount of phenylene rings added in the monomer: (poly(2,7-9,9?-dioctylfluorene-1,4-benzene) - oligomer 1 and (poly(2,7-9,9?-dioctylfluorene-p-quaterfenylene) - oligomer 2. Both materials were synthesized by Suzuki reaction and have their structural and photoluminescence properties studied. Moreover, measurements such as UV-Vis, FTIR, fluorescence, thermogravimetry, quantum yields, cyclic voltammetry and gel penetration chromatography were done. The results showed that the oligomers presents high quantum yield (65,2% to oligomer 1 and 85,6% to oligomer 2), the structure oligomer 1 is more rigid and oligomer 2 has more conjugation. In the second step of this work, the oligomer 1 (PF) was incorporated into an organic-inorganic hybrid matrix OIH based on di-ureasil host to evaluate the structure and optical properties of this new material. The synthesis was performed by sol-gel methodology, by incorporating different concentration of PF into the matrix (1, 5, 10 and 20 % of PF) (% w/w). The insertion of PF in the matrix HOI results in high quantum yields (44 % at 340 nm) and the synergism between PF and U(600) matrix observed by FTIR and Thermogravimetry. These properties show that the oligomers and the PF/HOI have potential application as photoluminescent material.